Introduction of the Indo-West Pacific mantis shrimp, Oratosquillina interrupta (Kemp, 1911) (Stomatopoda, Squillidae), to Brazil - Masunari, Setuko; Lopes, Odete Lopez; Ahyong, Shane T. (Zootaxa, 2025)
The Indo-West Pacific mantis shrimp, Oratosquillina interrupta (Kemp, 1911), is recorded for the first time from the Brazilian coast and Atlantic Ocean. A total of 39 specimens (4 males and 35 females) of O. interrupta were obtained during trawls for white shrimp fishing along Paraná State coast, southern Brazil in 2023 and 2024. Oratosquillina interrupta, now known from Brazilian waters, is the fourth species of the family Squillidae to become established outside of its native range.